A Study of the Effect of the Fringe Fields on the Electrostatic Force in Vertical Comb Drives - Else Gallagher; Walied Moussa (Sensors, 2014)
The equation that describes the relationship between the applied voltage and the resulting electrostatic force within comb drives is often used to assist in choosing the dimensions for their design. This paper re-examines how some of these dimensions—particularly the cross-sectional dimensions of the comb teeth—affect this relationship in vertical comb drives. The electrostatic forces in several vertical comb drives fabricated for this study were measured and compared to predictions made with four different mathematical models in order to explore the amount of complexity required within a model to accurately predict the electrostatic forces in the comb drives.